A Systematic Review: Evaluasi Terhadap Kejadian Perdarahan Pada Pasien ACS dengan Terapi Antiplatelet Tunggal Dibandingkan Terapi Antiplatelet Ganda Pasca Percutaneous Coronary Intervention (PCI) - Allysia Maria Vianney Putri; Rini Noviyani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Acute Coronary Syndrome (ACS) is a cardiovascular disorder with a high global mortality rate, including in Indonesia. Antiplatelet therapy administered either as monotherapy or as Dual Antiplatelet Therapy (DAPT) plays a crucial role in managing ACS patients after Percutaneous Coronary Intervention (PCI). However, such therapies carry a bleeding risk that requires careful evaluation. Previous studies on the pharmacological use of antiplatelet agents in post-PCI ACS patients have shown varying results. Therefore, this systematic review aims to compare the incidence of bleeding between single and dual antiplatelet therapies in ACS patients following PCI. Literature was retrieved from PubMed and Google Scholar using relevant keywords, resulting in 11 articles that met the inclusion criteria for further analysis. The reviewed studies include meta-analyses, randomized controlled trials (RCT), and cohort studies. Findings indicate that P2Y12 inhibitor monotherapy following short-term DAPT significantly reduces bleeding risk without increasing ischemic events, particularly in high-risk patients. This treatment strategy demonstrates better safety and comparable efficacy when compared to prolonged DAPT. This review is expected to serve as a reference for selecting safer and more appropriate antiplatelet therapy for ACS patients post-PCI, and as a foundation for future clinical policy development.